Lagina ve Ionia Rönesansı: Tapınak ve Propylon’daki Uygulamalar Işığında Ionia Rönesansı’nın Kronolojik Tanımlamasına Yeni Bir Katkı | Lagina and the Ionian Renaissance: A New Contribution to the Chronological Definition of the Ionian Renaissance in Light of the Construction Techniques in the Temple of Hecate and Propylon - Aytekin BÜYÜKÖZER (Arkhaia Anatolika, 2019)
“lonian Renaissance” is characterized by a revival of Archaic Anatolian architecture influenced by both contemporaneous mainland Greek architecture and substantial technical features introduced by the Hekatomnids and their architects. In this period, new construction programs were undertaken in many cities, and some characteristic construction techniques came to the forefront in these new buildings, such as the double-binder system in the corners, the Karian-Ionian lewis holes, and visible dovetail clamps, which are generally applied on stairs and stylobate blocks. Even though the chronological boundaries of the Ionian Renaissance cannot be precisely defined, the generally accepted view is that it started during the reign of Mausolus and continued until about 200 BC. The Karian-Ionian lewis holes, one of the characteristic applications of the Ionian Renaissance, were used in the Temple of Hecate and visible dovetail clamps were used in the Propylon. The fact that these techniques, which are chronologically limited to about 200 BC, are seen in the temple dating back to the late Hellenistic period and in the Propylon dating back to the early imperial period makes the applications in Lagina important. Researchers have assumed the use of these technical details in Lagina to be evidence that the structures belong to an earlier period or early stages of construction. However, such an association is not possible when the inscriptions in the sacred area, stylistic conventions on the architectural decorations of the structures and the historical course of Stratonikeia and Lagina are considered. It should not be concluded from the uses in Lagina that the temple dates back to an earlier date due to the Karian-Ionian lewis cuttings and the Propylon dates back to an earlier date due to the visible clamps. Here, it should be concluded that these techniques continued to be used long after 200 BC as they were applied in the structures dating back to the late Hellenistic and early imperial periods.